Recepção e circulação de testes de inteligência na escola de aperfeiçoamento de professores de Belo Horizonte (1929-1946) - César Rota Júnior (2016)
The entry of scientific psychology in Brazil had school education as a privileged field of application. In the first decades of the twentieth century, a set of educational reforms occurring in several states, including Minas Gerais, gave rise to the formation of psychology laboratories and a set of practices that had, as theoretical and methodological reference, a psychology which sought constitute and strengthen themselves as science. The objective of this study was to describe and analyze thereception and circulation of intelligence tests from its use in Belo Horizonte Teachers College, during its period of operation, from 1929 to 1946. Through a historiographical study, was possible to identify about 30 tests, were these intelligence tests or pedagogical tests. The analyzed data are presented in four complementary studies, we were seek to highlight the process of reception/circulation of intelligence tests. Thisconcept, arising from the field of literature, believes that the process of receiving a cultural artifact occurs actively, and not from a passive attitude in relation to the appropriate device, allowing the study of the relationship between the global and the local in establishment of new scientific instruments. It was possible to demonstrate how such a process was broader than the simple translation of foreign tests by teachers andstudents of the Belo Horizonte Teachers College. There, were produced new tests, which to a greater or lesser degree took foreign instruments as a reference, but adapted to local needs, contributing to the establishment of psychology as an independent science in the country. It was also possible to identify a pragmatic use of tests in the educational context, since priority was given to implementation of the instruments ineveryday school life at the expense of theorizing about the construct intelligence. This pragmatic use had, as a consequence, their use as more didactic and pedagogical tool in the training of students-teachers, than production of science. This way, we concluded that the Belo Horizonte Teachers College was, in fact, an adaptation workspace anddevelopment of new intelligence tests, which were used in the routine of school groups in the city and in the training of students-teachers.